Business transformation: habilitando a transforma????o por meio do Disruption Process Management (DPM) - Leite, David Tim??teo Carrilho (2017)
In times when business cycle of life is changing, socio-environmental demands gain space in global agenda, technology is also unsettling the relationship among organizations, competitors and customers. Business Transformation is coming to assist companies in transforming their business into this new structure. In this study, shows the creation of a new framework that helps organizations in their process of transformation, enabling them to keep safe in a disruptive technological world, without forgetting socio-environmental demands, it means a new concept called Disruption Process Management (DPM). DPM brings together the main advisors to the transformation of Business Process Management (BPM), Sustainable Development (SD) and Digital Economy (DE), in order to help companies to move towards higher stages of transformation. This new model uses BPM as a basis to restructure organizations' operations. Then, DE concepts are necessary to get about business model and consolidate organizations in the market, focusing on prosumers and digital management. While expansion occurs, organizations need to position themselves regarding socio-environmental issues, so as not to tarnish their reputation and brand. DPM concepts were applied by a study to an Insurer, named Company X's for purposes of confidentiality. That company already has a History of transformations and must keep its competitiveness. As result of this study, it was developed a method of analysis in which it was possible to identify the stage of the organizations transformation the gaps between theory and practice, effectively helping application of BPM, SD and DE, in a practical way. This paper is about a deep research of on Business Transformation in Brazil and is defines a structured method to propose improvements in business management, considering typical internal and external factors of 21st century. As theoretical contribution, it updated the processing model stages from Mckeown and Philip (2003).